The Effects of Different Levels of Dietary Metabolizable Energy and Copper-Methionine Supplementation on the Performance of Laying Hens - Anyetullah , Janat; Zia, Ziauddin (Journal of Natural Sciences – Kabul University, 2024)
This research aimed to investigate the effects of varying levels of metabolizable energy and copper-methionine supplementation in feed on the performance of laying hens. A total of 144 Nick Chick leghorn laying hens were utilized in a 3×3 factorial experiment within a completely randomized design (CRD). The study included 9 treatments, each with 4 replications and 4 hens per replication. Data obtained from the experiment were analyzed using SAS software version 9.1. The findings indicate that copper-methionine supplementation can be used to enhance chicken performance when high-energy feeds are employed in the management of laying hen flocks. Energy is the primary factor determining feed intake in birds and, in adult laying hens, serves as the key determinant of egg production levels. The results revealed that throughout the experimental period, the different levels of metabolizable energy and copper-methionine supplementation significantly influenced (P<0.05) feed consumption and the feed conversion ratio. However, their effects on other performance traits were not statistically significant (P>0.05). The experimental treatments significantly affected (P<0.05) egg volume and feed conversion ratio, while their impact on other yield traits remained non-significant (P>0.05).